The Utilization of Citronella (Cymbopogon nardus) Oil and Butterfly Pea Flower Extract in The Production of Mosquito Repellent Lotion - Desy Triastuti; Enceng Sobari; Wihartini Wihartini (Agroindustrial Technology Journal, 2024)
Citronella is an essential oil-producing plant that has the potential to be used as a mosquito repellent agent since it contains citronellal, citronellol and geraniol components. The aim of this research was to determine the physicochemical and organoleptic characteristics of mosquito repellent lotion prepared from citronella oil and butterfly pea flower extract. A completely randomized design of 4 treatments of citronella oil (0%, 2%, 4%, and 6%) and 3 replications was used in this study. The parameters observed include physicochemical characteristics (spreadability, protection, emulsion stability, and pH) and organoleptic (level of preference for color, texture, aroma, and sticky impression) of repellent. The data was analyzed using the One Way ANOVA followed by DNMRT at 5% significance level. The results showed that the use of citronella oil gave a significant difference inphysicochemicalcharacteristics (spreadability, protection ability, emulsion stability, the pH value) and organoleptic (level of preference for color and texture) of mosquito repellent lotion. However, it had no significant result to the preference of the aroma and the impression of stickiness. The pH values of the lotion were above the standard value required by SNI. The best protectionabilityof the lotion was treatment 6%yet it had a texture issue, so it needs to be improved.